Effectiveness Of Teaching Arabic Language To Different Knowledge Background Students/ فعالية تدريس اللغة العربية للطلاب الذين هم ذوو الخلفية المعرفية المتباينة - Mohammed Cassim Sithy Shathifa; Mohammed Haneefa Abdul Munas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Managing a classroom consisting of students with different background knowledge in language skills has become difficult for Arabic language teachers in state universities in Sri Lanka, which has led to poor achievement in the four skills of students, in addition to that teachers face difficulty in achieving the desired goal of the lesson during the assigned class. This study aims to expose the current situation of the process of teaching Arabic in state universities in Sri Lanka, to reveal the reality of Arabic language teachers in taking into account individual differences, and to determine the extent of the students’ weak performance of language skills, and to diagnose its causes affecting it. The effect of the cognitive level variable on students’ linguistic achievement and to know the reality of teachers in the issue of taking into account individual differences. The researcher used descriptive quantitative methodology to analyse the data gathered through structured questionnaire and library works by using MS Excel. The study reached several results such as; the current curriculum in the Department of Arabic Studies is not designed in the light of psychological and social principles, and that the classroom may consist of students of different levels in age and knowledge, and there is a lack of interest among teachers with regard to taking into account individual differences. The responsible persons should consider reformulating the curriculum in accordance with modern requirements in light of psychological and social principle.